THE IMPACT OF DIFFERENT SEEDING DATES ON SEED YIELD OF SOYBEAN - D. Karaaslan; M. Hakan; R. Ekinci; E. Boydak (Journal of Animal and Plant Sciences, 2012)
This study was conducted to determine the effect of six different seeding dates (15th April, 1st May, 15th May, 1st June, 15th June and 30th June) on the yield and yield components of the soybean. The experimental design was a randomized complete block with split plot having four replicates. The studies were conducted at GAP International Agricultural Research and Training Center in 2004, 2005 and 2006 years. The results indicated that the cultivars were significantly influenced by the different seeding dates for the traits of plant height (PH), first pod height (FPH), pod number (PN), weight for 100 seeds (SW), seed yield (SY), oil yield (OY) and protein yield (PY), It was observed that cv. NE3399 had the highest seed yield while the lowest seed yield was given by UMUT2002.
Keywords: Soybean; Seeding Date; Seed; Oil and Protein Yield.